Pengaruh Model Pembelajaran TKN Berbantuan Komik Digital Terhadap Pemahaman Konsep Nilai-Nilai Pancasila Siswa Kelas IV SDN 4 Banyuasri - Widiastini, Ni Wayan Eka; Rati, Ni Wayan; Sukmayasa, I Made Hendra (Program Studi PGMI, Universitas Al Falah As Sunniyah Kencong Jember, 2025)
The aims of this research is to analyze the effect of the TKN learning model assisted by digital comics on the understanding of Pancasila values among fourth-grade students at SDN 4 Banyuasri. This study is a quasi-experimental research using a One Group Pretest-Posttest Design. The independent variable in this study is the TKN learning model assisted by digital comics, while the dependent variable is the students' understanding of Pancasila values. The population, which also serves as the sample in this study, consists of 38 fourth-grade students at SDN 4 Banyuasri. The research consists of three stages: the preparation stage, the implementation stage, and the final stage of the research. The data collection method used is the test method. The instrument used is an essay test related to the material on Pancasila values. The data analysis methods employed are quantitative descriptive analysis and inferential analysis using one-way ANOVA. Based on the research conducted, it can be concluded that there is a significant effect of the TKN learning model assisted by digital comics on the understanding of Pancasila values among fourth-grade students at SDN 4 Banyuasri, with an F-value of 49.684 and a significance level of 0.000.